Răspuns :
a : b = 3 rest 2
b : c = 3 rest 2
a - c = 336
a + b + c = ?
a = 3b + 2
b = 3c + 2
c = a - 336
b = 3 * (a - 336) + 2
b = 3a - 1008 + 2
b = 3a - 1006
a = 3 * (3a - 1006) + 2
a = 9a - 3018 + 2
- 8a = - 3016
a = 3016 : 8
a = 377
c = 377 - 336
c = 41
b = 3 * 41 + 2
b = 123 + 2
b = 125
a + b + c = 377 + 125 + 41= 543
b : c = 3 rest 2
a - c = 336
a + b + c = ?
a = 3b + 2
b = 3c + 2
c = a - 336
b = 3 * (a - 336) + 2
b = 3a - 1008 + 2
b = 3a - 1006
a = 3 * (3a - 1006) + 2
a = 9a - 3018 + 2
- 8a = - 3016
a = 3016 : 8
a = 377
c = 377 - 336
c = 41
b = 3 * 41 + 2
b = 123 + 2
b = 125
a + b + c = 377 + 125 + 41= 543